The Structure of Simple and Coordinate Phrase in terms of Constituent and Deletion - abuzeid, sanya jebar (Humanities Journal of University of Zakho, 2022)
Types of phrase-structure is the important subject in a syntactic level and in terms of constituent، is one of the ways of identifying the phrase-structure in the Kurdish language( Kurmanji-Bahdini sub-dailect). in terms of existence، each of the simple and Coordinate phrase-structure is also divided into two types such as noun phrase and preposition phrase. This study is conducted based on the Analytical – Descriptive method in the light of the generative theory and transformation. The importance of this study is that it is an attempt to demonstrate the phrase structure by type of constituents category (head، determiner and complement) to identify the number and order structure. In the other hand، the importance of this study is to demonstrate deletion of the structure in terms of the deep structure of the phrase. The main aim of this study is identify the relationship that is between of the different constituent phrase and different structure phrase since the number، type، and order of the constituent effects the structure of simple phrase and deletion. it also illustrates the deletion of that constituents in which it is capable to be deleted in that phrases because all the types of constituent are incapable to be deleted in that phrases. Keywords: Structure، Constituent، Simple Pharse، Coordinate phrase، Deletion.